Mild COVID-19 and Impaired Blood Cell–Endothelial Crosstalk: Considering Long-Term Use of Antithrombotics? - Melkumyants, Arthur; Buryachkovskaya, Ludmila; Lomakin, Nikita; Antonova, Olga; Serebruany, Victor (Thrombosis and Haemostasis, 2021)
Background Current coronavirus disease 2019 (COVID-19) pandemic reveals thrombotic, vascular, and endothelial dysfunctions at peak disease. However, the duration, degree of damage, and appropriate long-term use of antithrombotic strategies are unclear. Most COVID data are yielded from random clinical observations or autopsy of postmortem samples, while precise blood cellular data in survivors are insufficient.Methods We analyzed erythrocytes, circulating endothelial cells, and echinocytes by electron microscopy and flow cytometry in patients with confirmed COVID-19 (n = 31) and matched healthy controls (n = 32) on admission and at hospital discharge.Results All patients experienced mild disease, none required pulmonary support, and all survived. Admission number of circulating endothelial cells was significantly (40–100 times) higher in COVID-19 patients. Cells were massively damaged by multiple fenestrae in membranes with diameter comparable to the size of supercapsid in SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) virus. COVID-19 also provoked formation of stacked aggregated erythrocytes capable of clogging microvascular bed and of diminishing oxygen supply. In some patients, such abnormalities persisted at hospital discharge revealing remaining intracellular penetration of SARS-CoV-2 where it may be replicated and returned to circulation.Conclusion These observational and descriptive data suggest that persistent viral cell injury may cause blood vessel damage; their increased permeability resulted in tissue edema, inflammation, platelet activation, and augmented thrombosis. There is a residual blood cell damage following the acute phase in some COVID-19 survivors. Controlled outcome-driven trials are urgently needed for exploring optimal use of long-term antithrombotics and vascular protection strategies even after mild COVID-19.
Keywords: COVID-19; circulating endothelial cells; erythrocytes; echinocytes; electron microscopy; flow cytometry